Impact of 12‐hr shifts in general hospitals: Study conducted in two intensive care units - Anne Fratissier; Philippe Gauberti; Rémy Morello; Bénédicte Clin (Wiley, 2021)
Abstract Aim To evaluate the impact of 12‐hr shifts on health status, working conditions and satisfaction among nurses and healthcare auxiliaries in medical and surgical intensive care units in a general hospital. Design This study was a descriptive and prospective questionnaire study of personnel involved in the organization of 12‐hr shifts. Methods The EVREST questionnaire was used, with the addition of two questions on respondents' health status and five questions on their job satisfaction. The study consisted of a first phase immediately before work was organized in 12‐hr shifts and a second within 7-9 months of application of this organization. Results Positive effects were found among day nurses including decreased periods of pressure during the working day and improved work-life balance. Conversely, night nurses, who are not in favour of 12‐hr shifts, reported dissatisfaction caused by a deterioration both in working conditions and in work-life balance.